If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 + 2x + -5 = 6 Reorder the terms: -4 + -5 + x + 2x = 6 Combine like terms: -4 + -5 = -9 -9 + x + 2x = 6 Combine like terms: x + 2x = 3x -9 + 3x = 6 Solving -9 + 3x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3x = 6 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 6 + 9 3x = 6 + 9 Combine like terms: 6 + 9 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 5p-4p-(p-2)=3(p+4) | | 2x(9+h)=20 | | 24x+72x-14-6x+26= | | 2u^2+5uv+2v^2=0 | | M=-0.3n+21 | | x-0.2=3 | | -15z=60 | | 8x-(3x+2)=1 | | 0.50x+0.20y=4.20 | | 6x^2-22x-12=0 | | y^2-12y+20=0 | | 13x-3=14x | | x-9=32 | | 2x^5-6=17 | | 2q+11+15=22+q+20 | | 4a-15=-23 | | 2xy-3y^2=0 | | 21s=3 | | X^2-16x+28= | | 4x^2-12xy+9y^2=0 | | y=1-3 | | q-13=-13 | | y=0-3 | | 5p=3p+22 | | 16-2y=1 | | 2x^4=162 | | 15-5z=0 | | 8c+16=5c-8 | | 4(x+3)=1 | | y=-3-3 | | 13t+19+9=38+t+14 | | -3=y-3 |